2021
DOI: 10.14405/kjvr.2021.61.e10
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of toceranib phosphate (Palladia) for treatment of different tumor types in 31 dogs

Abstract: The purpose of this retrospective study was to provide additional data on the use of toceranib in a wide variety of tumor types in small breed dogs, especially < 8 kg (except 5 dogs). This was a retrospective study of 31 dogs with malignant tumors treated with a 2.5 mg/kg median dose of toceranib (Palladia; Zoetis, USA) on a Monday-Wednesday-Friday schedule. Clinical benefit was observed in 13 of 15 dogs (86.7%, 3 with complete response, 4 with partial response, 6 with stable disease) with gross disease. Dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Toceranib phosphate inhibits both normal and mutated tyrosine kinase receptors by competitive inhibition of adenosine triphosphate binding, which is needed for phosphorylation and downstream signaling. The targets of toceranib are split-kinase family elements such as the FMS-like tyrosine kinase-3, KIT, vascular endothelial growth factor receptor 2, and platelet-derived growth factor receptor β ( 16 ). These drugs offer different options for mechanisms for cancer cell death at different molecular levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toceranib phosphate inhibits both normal and mutated tyrosine kinase receptors by competitive inhibition of adenosine triphosphate binding, which is needed for phosphorylation and downstream signaling. The targets of toceranib are split-kinase family elements such as the FMS-like tyrosine kinase-3, KIT, vascular endothelial growth factor receptor 2, and platelet-derived growth factor receptor β ( 16 ). These drugs offer different options for mechanisms for cancer cell death at different molecular levels.…”
Section: Discussionmentioning
confidence: 99%
“…We believed that the combination of vincristine and toceranib increases the antitumor activity because toceranib inhibits both normal and mutated tyrosine kinase receptors that are needed for phosphorylation and downstream signaling, kills tumor cells, and decreases the blood supply to the tumor because of its antiangiogenic effect ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of attention has also been directed towards the use of TKRi in combination with standard of care. One of the most relevant TKRi in veterinary clinics is toceranib phosphate (Palladia), which is a multi-target TKRi that acts against vascular endothelial growth factor receptor (VEGFR), platelet-derived growth factor receptors (PDGFR), c-Kit, colony-stimulating factor 1 receptor (CSF1R) and fms-like tyrosine kinase (FLT3), which are commonly altered in many cancers, including OSA [88]. It has been suggested that the use of toceranib phosphate, in combination with chemotherapy, may be effective in treating canine metastatic OSA with high PDGFR, VEGFR2 and c-Kit expression [42,43].…”
Section: In Vivo Canine Osa Modelsmentioning
confidence: 99%